2014
DOI: 10.1016/j.actbio.2013.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium alloys as a biomaterial for degradable craniofacial screws

Abstract: Recently, magnesium (Mg) alloys have received significant attention as a potential biomaterial for degradable implants, and this study was directed at evaluating the suitability of Mg for craniofacial bone screws. The objective was to implant screws fabricated from commercially available Mg-alloys (pure Mg and AZ31) in-vivo in a rabbit mandible. First, Mg-alloy screws were compared to stainless steel screws in an in-vitro pull-out test and determined to have a similar holding strength (~40N). A finite element … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 40 publications
1
97
0
2
Order By: Relevance
“…In the lot L5, L3 and L4 a significant hypo-phosphatemia was registered (p < 0.05; n = 5) in the second week from the implantation, while in the fourth week the blood phosphate concentration reached values close to control for L5 and L4 groups but not for L3. These variations can be explained by considering the differences between the implants sample: Mg-Ca-Si with Si concentration gradient implant (L3 group) presented in vivo a slower biodegradation process as compared with Mg-Ca-Si implant without Si concentration gradient (L4 group), similar observation being reported by [22,27,28].…”
Section: The Main Blood Biochemical Markers In Rats With Tibiae Implantsupporting
confidence: 80%
“…In the lot L5, L3 and L4 a significant hypo-phosphatemia was registered (p < 0.05; n = 5) in the second week from the implantation, while in the fourth week the blood phosphate concentration reached values close to control for L5 and L4 groups but not for L3. These variations can be explained by considering the differences between the implants sample: Mg-Ca-Si with Si concentration gradient implant (L3 group) presented in vivo a slower biodegradation process as compared with Mg-Ca-Si implant without Si concentration gradient (L4 group), similar observation being reported by [22,27,28].…”
Section: The Main Blood Biochemical Markers In Rats With Tibiae Implantsupporting
confidence: 80%
“…In previous study, numerous studies have been focusing on the degradation performance of Mg-based screws inserted to intact host bone, i.e. AZ31 screw in rabbit mandible [29] and sheep hip bone [30], MgCa0.8 alloy screws in rabbit tibiae [31], which performed a in vivo stale and gradual corrosion rate. Furthermore, Gu et.al [12] and Kannan et.al [32] revealed corrosion promotion of Mg-based materials (as cast AZ91D, as extruded As the corrosion proceeds, the degeneration of mechanical integrity was expected.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Histological examination also showed matured bone tissue ingrowth in HP Mg screw. Much evidence proved good osseointegration and bone ingrowth around Mg alloy screws[29,30,38]. Therefore, it was supposed Mg ion, which evolved during thedegradation of the Mg material, significantly affected the osteogenic differentiation of the surrounding tissue.…”
mentioning
confidence: 98%
“…The feed rate parameter has strong correlation to surface texture. As stated by previous researcher that nose radius and feed rate have a significant correlation to surface texture of new machined surface when machining super alloy materials [10]. Meanwhile, Gusri, et.al [9] found that when machining super alloy material, surface texture of machined surface formed were affected by worm tool.…”
Section: Feed Marks On the Machined Surface Of Magnesium Alloy Aftermentioning
confidence: 77%